Kwietnica okazała Protaetia speciosissima (Scopoli, 1786) (Coleoptera: Scarabaeidae) – chroniony gatunek saproksyliczny drzewostanów dębowych w Polsce - Plewa, Radosław; Hilszczański, Jacek; Jaworski, Tomasz; Tarwacki, Grzegorz (Leśne Prace Badawcze, 2014)
The paper presents the results of our studies on the preferences of the flower chafer, Protaetia speciosissima (Scopoli, 1786). The studies were carried out in 2009-2010 in the Forest Districts of Hajnówka, Krotoszyn, Łochów, Pińczów, and Puławy, located in various regions of Poland. Barrier traps consisting of a Moericke’s trap and a Malaise’s trap combined with a barrier of fine net were used to collect beetles. Traps were installed at two heights in over 100 years old oak stands, with the upper level in the canopy layer (mean height of 20.5 m) and the lower level adjacent to the tree trunk (mean height of 4,5 m). During two-year study, we collected a total of 328 specimens of P. speciosissima , 299 from the upper- and 29 from the lower forest layer. Thus, we confirmed strong preferences of the adult of P. speciosissima for the canopy layer in oak stands. Furthermore, our observations on phenology indicate that the second half of June and all of July are the months with the highest population density of P. speciosissima . This paper also proposes modes of action for conservation of the species.